Megacities and High Speed Rail systems: which comes first? - Pagliara, Francesca; Abreu e Silva, Joao de; Sussman, Joseph; Stein, Naomi (My University, 2013)
In Europe it is rare to find megacities, apart from London and Paris, both of them megacities for reasons other then the existence of High Speed Rail (HSR). However, due to the general high density of population in Europe and the short distance between medium and large cities HSR can act as a catalyst for the emergence of groups of cities that will be linked together. Thus, with the help of HSR Europe can reap the economic benefits associated with megacities, namely economies of scale, economies of agglomeration and bigger labour markets. This is important because adequate levels of planning might help to avoid the costs of megacities in these European locations. However, in this contribution the authors argue that in some cases, specific facilities can foster the formation of megacities; in fact, this is the case of High Speed rail systems (see for example, Europe). Specifically, High-Speed trains can be used to solve two different accessibility problems. In the first case, where a point-to-point link is dominant, each train is a potential substitute for an air connection between two cities, i.e. it connects cities (or rather central business districts -CBDs) located far apart with a direct train connection. The HSR links between Paris and Lyon, Paris and London and, Tokyo and Osaka, could be seen as examples of this first type of train connection. In this case the train trip together with access and egress times should be compared with the competing solution which consists of the air trip plus the trip to the airport at the trip origin and the trip from the airport at the trip destination. In the second case, where a HSR network is dominant, the rail system links together many cities and CBDs and, hence, creates a new type of region with a high intra-regional accessibility sharing a common labour market and a common market for household and business services. In this case the HSR binds together cities in a band, where each pair of cities is at a time distance of between 20 minutes and 1 hour, i.e. a time distance that allows daily commuting. For example, in Germany and Italy a number of cities are connected in exactly this manner by HS train. In the U.S., HSR projects are very recent and they will have the rote of connecting already formed megacities. An example is the state of California, which is planning an 800-mile HSR service connecting Los Angeles and San Francisco in a two and a half hour trip.
Keywords: Verkehr; Eisenbahnverkehr; Megacity; Fernverkehr; Personenverkehr; Standortfaktor; Reisezeit; Hochgeschwindigkeitsstrecke